2000
DOI: 10.1007/pl00008655
|View full text |Cite
|
Sign up to set email alerts
|

Three-partner conversion induced by the P-element transposase in Drosophila melanogaster

Abstract: Conversion of one P-derived transposon into another has already been shown to occur with a measurable frequency. However, the mechanism responsible for such replacements has remained controversial. We previously proposed a mechanism involving three partners. We assumed that after excision of the P-element inserted at the target site, the double-strand break was repaired using, first, the homologous P sequences on the sister chromatid, and second, a remote template, the donor P-derived transposon. However, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…At least four distinctive exit strategies to avoid silencing-induced sequence erosion are known: (1) the resurrection of silenced transposons by means of interelement selection and ectopic recombination between distinct subfamily members (Jordan and McDonald 1998), (2) the reactivation of silenced genomic parasites by stochastic loss of host-encoded suppressor alleles (Pelisson et al 1994;Prud'homme et al 1995), (3) the escape via horizontal transfer into the naive genome of an unprotected host species (Flavell 1999), and (4) molecular domestication see below). Recombination between different elements has been observed recently, first in retrotransposons (Jordan and McDonald 1998;Saxton and Martin 1998), retroviruses such as HIV (Gao et al 1998;Laukkanen et al 2000), and also in DNA transposons (Miller et al 1999;Peronnet et al 2000). Sequence analyses of genomic parasites derived from yeast, Drosophila, mouse, and humans have shown that new active copies were generated by ectopic recombination between different variants present in the genome.…”
Section: Vertical Inactivationmentioning
confidence: 95%
See 1 more Smart Citation
“…At least four distinctive exit strategies to avoid silencing-induced sequence erosion are known: (1) the resurrection of silenced transposons by means of interelement selection and ectopic recombination between distinct subfamily members (Jordan and McDonald 1998), (2) the reactivation of silenced genomic parasites by stochastic loss of host-encoded suppressor alleles (Pelisson et al 1994;Prud'homme et al 1995), (3) the escape via horizontal transfer into the naive genome of an unprotected host species (Flavell 1999), and (4) molecular domestication see below). Recombination between different elements has been observed recently, first in retrotransposons (Jordan and McDonald 1998;Saxton and Martin 1998), retroviruses such as HIV (Gao et al 1998;Laukkanen et al 2000), and also in DNA transposons (Miller et al 1999;Peronnet et al 2000). Sequence analyses of genomic parasites derived from yeast, Drosophila, mouse, and humans have shown that new active copies were generated by ectopic recombination between different variants present in the genome.…”
Section: Vertical Inactivationmentioning
confidence: 95%
“…Hybrid elements of DNA transposons were detected recently. In D. melanogaster the resurrection of an active canonical P element through recombination of defective copies has been described by Peronnet et al (2000). In the obscura group, sequence comparisons indicate a hybridogenic origin of the T-type P elements (Miller et al 1999).…”
Section: Vertical Inactivationmentioning
confidence: 97%